Complement C1q essential for aeroallergen sensitization via CSF1R+ conventional dendritic cells type 2 - Moon, Hyung-Geun; Eccles, Jacob D.; Kim, Seung-jae; Kim, Ki-Hyun; Kim, Young-Mee; Rehman, Jalees; Lee, Hyun; Kanabar, Pinal; Christman, John W.; Ackerman, Steven J.; Ascoli, Christian; Kang, Homan; et al. (Journal of allergy and clinical immunology, 2023)
Dendritic cells (DCs) are heterogeneous, comprising multiple subsets with unique functional specifications. Our previous work has demonstrated that the specific conventional type 2 DC subset, CSF1R+cDC2s, plays a critical role in sensing aeroallergens. It remains to be understood how CSF1R+cDC2s recognize inhaled allergens. We sought to elucidate the transcriptomic programs and receptor-ligand interactions essential for function of this subset in allergen sensitization. We applied single-cell RNA sequencing to mouse lung DCs. Conventional DC-selective knockout mouse models were employed, and mice were subjected to inhaled allergen sensitization with multiple readouts of asthma pathology. Under the clinical arm of this work, human lung transcriptomic data were integrated with mouse data, and bronchoalveolar lavage (BAL) specimens were collected from subjects undergoing allergen provocation, with samples assayed for C1q. We found that C1q is selectively enriched in lung CSF1R+cDC2s, but not in other lung cDC2 or cDC1 subsets. Depletion of C1q in conventional DCs significantly attenuates allergen sensing and features of asthma. Additionally, we found that C1q binds directly to human dust mite allergen, and the C1q receptor CD91 (LRP1) is required for lung CSF1R+cDC2s to recognize the C1q-allergen complex and induce allergic lung inflammation. Lastly, C1q is enriched in human BAL samples following subsegmental allergen challenge, and human RNA sequencing data demonstrate close homology between lung IGSF21+DCs and mouse CSF1R+cDC2s. C1q is secreted from the CSF1R+cDC2 subset among conventional DCs. Our data indicate that the C1q-LRP1 axis represents a candidate for translational therapeutics in the prevention and suppression of allergic lung inflammation.